Anatomical Identification of Leaf Stomatal Cell Types in The Family Euphorbiacea - Miduk Leonardo Tambun; Sirem Suri; Lili Anna Sari Siregar; Siti Rhadiatun Mardiah; Tri Mustika Sarjani (Jurnal Biologi Tropis, 2023)
Stomata, which are specialized cells on the surface of leaves, undergo modification to form structures containing two guard cells. These cells play a crucial role in facilitating the exchange of water vapor and gases between the plant's internal environment and the surrounding atmosphere. Typically located on plant parts exposed to air, such as leaves, stems, and rhizomes, stomata distribution varies among different species. While some plants exhibit stomata on both upper and lower leaf surfaces, others, like water lilies, exclusively feature stomata on the upper side.The objective of the current investigation was to analyze the stomatal anatomy of various plant species within the Euphorbiaceae family. Employing a qualitative descriptive approach, the study aimed to characterize and interpret the stomatal types present on the leaves of Euphorbiaceae plants in the Langsa City region. The findings revealed the presence of five Euphorbiaceae species in Langsa City, including Euphorbia mili (jade fern), Jatropha curcas (Jatropha curcas), Codiaeum variegatum 'Norma' (norma puring), Codiaeum variegatum Bi (jet puring), and Codiaeum finger (finger puring), all of which exhibited parasitic stomatal types.